Peningkatan Kompetensi Guru dan Siswa SMK Negeri 3 Jayapura Lewat Pelatihan Teknologi Digital dan Pengembangan Perangkat Praktikum - Handoko Handoko; Yakobus Kariongan; Tiper Korneles Muwarberto Uniplaita (Fakultas Teknik Universitas Cenderawasih, 2025)
SMK Negeri 3 Jayapura is one of the vocational schools specializing in technology engineering in Jayapura City. There are three primary issues at SMK Negeri 3 Jayapura. First, the limited competence of teachers in microcontroller programming. Second, there is a lack of facilities and infrastructure for microcontroller practical work. Third, the low achievement and interest of students in the latest technological developments. The proposed solutions in this community service activity include: conducting training on Arduino Uno and Espressif microcontrollers using the Arduino IDE programming platform, developing practical modules for microcontrollers, sensors, and actuators, providing a master file for Arduino Uno programs, installing the necessary software on school computers, conducting robotics training for students. All five solutions were successfully implemented and received positive appreciation from both students and teachers at SMK Negeri 3 Jayapura.